Motivasi Perempuan Pelaku Pembunuhan (Studi Kasus pada Lembaga Pemasyarakatan Perempuan Kelas IIA Palembang) - Nabila Nabila (Wajah Hukum, 2021)
Prisoners' life is a pattern of activities or activities carried out for inmates and grouped in a place that is not free (movement) as a form of being responsible for all their actions in order to lead them to correct actions according to law and religion in the hope that they can repent and regret everything his actions when he is free later. The term for female prisoners who are fostered in a correctional facility is a prisoner or a correctional client. The crime of murder committed by a woman is indeed very hard to believe during human civilization on this earth. The life that is lived by a female prisoner in a correctional facility often causes her to face various psychological problems, including the loss of her personality as a result of rules and ways of life that are very different from life lived outside the Penitentiary. This study aims to determine what the motivation of a woman to commit a murder crime and how to deal with the psychological conditions of female prisoners who commit a murder crime.